Sharah Hadith about Sutrah Prayer in the View of the Ulama - Muhammad Fikri Firdaus; Yumna Yumna (Gunung Djati Conference Series, 2021)
This study aims to explain the use of the sutrah prayer according to the hadith. This research is a qualitative type that applies literature study, sharah hadith method, and content analysis. The results and discussion of this research include the definition of the sutrah prayer, the use of the sutrah prayer according to the hadiths, the traditions about the form of the sutrah prayer, as well as the views of the scholars about the syarah hadith. This study concludes that the diversity of Muslim understanding in responding to the hadiths about the sutrah prayer is a subject that can be resolved by Islamic law. Moreover, a moderate compromise of views on the diversity of Muslim understanding on the topic is again very possible by committing sharah to the intended hadith through a comprehensive multi-approach, particularly the approach of religious, hadith, and social studies. This study recommends further research on sutrah in prayer in the form of field studies with the same approach and further developed.